Racial/Ethnic Differences in the Development of Disability Among Older Adults - Dunlop, Dorothy D. (American Public Health Association, 2007)
Objectives. We investigated differences in the development of disability in activities of daily living among non-Hispanic Whites, African Americans, Hispanics interviewed in Spanish, and Hispanics interviewed in English. Methods. We estimated 6-year risk for disability development among 8161 participants 65 years or older and free of baseline disability. We evaluated mediating factors amenable to clinical and public health intervention on racial/ethnic difference. Results. The risk for developing disability among Hispanics interviewed in English was similar to that among Whites (hazard ratio [HR]=0.99; 95% confidence interval [CI] = 0.6, 1.4) but was substantially higher among African Americans (HR=1.6; 95% CI=1.3, 1.9) and Hispanics interviewed in Spanish (HR=1.8; 95% CI=1.4, 2.1). Adjustment for demographics, health, and socioeconomic status reduced a large portion of those disparities (African American adjusted HR=1.1, Spanish-interviewed Hispanic adjusted HR=1.2). Conclusions. Higher risks for developing disability among older African Americans, and Hispanics interviewed in Spanish compared with Whites were largely attenuated by health and socioeconomic differences. Language- and culture-specific programs to increase physical activity and promote weight maintenance may reduce rates of disability in activities of daily living and reduce racial/ethnic disparities in disability.